IMPLEMENTATION OF INTEGRATED PJBL-STEM AND SEL TO ENHANCE STUDENTS CREATIVE THINKING SKILLS - Amelia Novita Sari; Agung Mulyo Setiawan; Sitti Djuwarijah (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
The ability to think creatively is a necessary skill for students as a basis for thinking, with indicators of fluency, flexibility, originality, and elaboration. Therefore, a learning design is needed as a solution to train students abilities in generating many ideas smoothly, providing unique ideas, and relating their learning experiences as 21st century competencies. This study aims to describe the implementation process of PjBL-STEM integrated with SEL using a mini-planetarium product and analyze its impact on improving students creative thinking skills during the learning process. The learning process was implemented through several stages orientation, planningand designing, project creation, testing and presentation, and evaluation. This research is a case study with a single case design, which consists of determining and defining questions, determining research design and instruments, determining techniques and collecting research data, and making a final report. Data collection techniques were conducted through interviews, observations, and student questionnaires. The research instruments used were interview guidelines, learning implementation observation sheets, and student reflection questionnaires. Data analysis techniques were carried out by applying qualitative descriptive analysis and percentage calculation. The findings indicate that integrating PjBL-STEM with SEL through the mini-planetarium project effectively enhanced students creative thinking, with the strongest gains observed in fluency (89%) and flexibility (81%), while originality (74%) and elaboration (71%) showed good progress but require further reinforcement. Results on the implementation process are still under analysis and will provide important insights for refining instructional design and future classroom applications.